Front Cover: AuNP‐Modulated qPCR: An Optimized System for Detecting MIR Biophotons Released in DNA Replication (Chem. Eur. J. 8/2023). Issue 8 (26th January 2023) - Yang, Yu; Peng, Daoling; Gu, Zhenglong; Jiang, Lei; Song, Bo
Abstract : ATP, the cell energy currency mostly produced by mitochondria, is conventionally regarded as releasing heat to drive biological reactions and processes. By employing dNTPs (i. e., energy molecules that have an identical way of storing/releasing energy to ATP), we demonstrated that ATP hydrolysis can release photons with a specific mid‐infrared frequency to efficiently drive DNA replication. More information can be found in the Research Article by L. Jiang, B. Song, and co‐workers (DOI: 10.1002/chem.202203513 ).